THE INFLUENCE OF CONTENT MARKETING, SALES PROMOTION, AND ADVERTISING ON PURCHASE INTENTION AT PT HILMASTA DIGITAL INDONESIA - Madeline Elizabeth; Alfonsius Alfonsius (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
People have been conducting business for centuries. The rivalry among businesses has risen over time, and each company has attempted to increase profits by finding new ways to enhance the business. The technological advancements have opened up new ways for marketing. Due to the evolving customer behavior, companies have attempted to adapt their marketing to the digital platform. One of the alternatives that has grown in popularity recently is online business. The purpose of this research is to know whether there is partial and simultaneous influence of content marketing, sales promotion, and advertising on purchase intention at PT Hilmasta Digital Indonesia. PT Hilmasta Digital Indonesia is a digital creative agency that creates creative content which can help small to medium business in Indonesia expand digitally. The sample for this research is 73 people, which was selected using the purposive sampling, also known as the judgmental sampling techniques. For data analysis in this study, quantitative descriptive and causal methods are used. Questionnaires are sent in order to collect the data. The data analysis method that is employed in this study is multiple linear regression. The F-test result demonstrates that Content Marketing, Sales Promotion, and Advertising have a simultaneous influence on the Purchase Intention at PT Hilmasta Digital Indonesia. The t-test result also reveals that Content Marketing has partial influence on Purchase Intention at PT Hilmasta Digital Indonesia, Sales Promotion has partial influence on Purchase Intention at PT Hilmasta Digital Indonesia, and Advertising has partial influence on Purchase Intention at PT Hilmasta Digital Indonesia. This research regression model demonstrates as Sales Promotion has a greater impact on Purchase Intention than Advertising and Content Marketing,